Effects of a hot ambient operating theatre on manual dexterity, psychological and physiological parameters in staff during a simulated burn surgery - Palejwala, Z.; Wallman, K.; Ward, M.K.; Yam, C.; Maroni, T.; Parker, Sharon; Wood, F. (PUBLIC LIBRARY SCIENCE, 2019)
© 2019 Palejwala et al. Objectives Hot environmental conditions can result in a high core-temperature and dehydration which can impair physical and cognitive performance. This study aimed to assess the effects of a hot operating theatre on various performance, physiological and psychological parameters in staff during a simulated burn surgery. Methods Due to varying activity levels, surgery staff were allocated to either an Active (n = 9) or Less- Active (n = 8) subgroup, with both subgroups performing two simulated burn surgery trials (CONTROL: ambient conditions; 23±0.2°C, 35.8±1.2% RH and HOT: 34±0°C, 28.3±1.9% RH; 150 min duration for each trial), using a crossover design with four weeks between trials. Manual dexterity, core-temperature, heart-rate, sweat-loss, thermal sensation and alertness were assessed at various time points during surgery. Results Pre-trials, 13/17 participants were mildly-significantly dehydrated (HOT) while 12/17 participants were mildly-significantly dehydrated (CONTROL). There were no significant differences in manual dexterity scores between trials, however there was a tendency for scores to be lower/impaired during HOT (both subgroups) compared to CONTROL, at various time-points (Cohen's d = -0.74 to -0.50). Furthermore, alertness scores tended to be higher/ better in HOT (Active subgroup only) for most time-points (p = 0.06) compared to CONTROL, while core-temperature and heart-rate were higher in HOT either overall (Active; p<0.05) or at numerous time points (Less-Active; p<0.05). Finally, sweat-loss and thermal sensation were greater/higher in HOT for both subgroups (p<0.05). Conclusions A hot operating theatre resulted in significantly higher core-temperature, heart-rate, thermal sensation and sweat-loss in staff. There was also a tendency for slight impairment in manual dexterity, while alertness improved. A longer, real-life surgery is likely to further increase physiological variables assessed here and in turn affect optimal performance/outcomes.